2019
DOI: 10.1039/c9gc02058f
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional phase-transfer catalysts for fixation of CO2 with epoxides under ambient pressure

Abstract: A series of bifunctional phase-transfer catalysts with a quaternary onium center and a hydrogen-bonding donor group were prepared for the fixation of CO2 with epoxides under mild conditions by using a CO2 balloon (1 atm) to produce cyclic carbonates up to 95% yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 82 publications
0
32
0
Order By: Relevance
“…More recently, Endo et al demonstrated that guanidinium iodide catalysts 32 were catalysts for the synthesis of cyclic carbonates under mild reaction conditions (1 bar carbon dioxide, 25 o C, 24 h, 5 mol% catalyst). 81 In 2019, Wang et al prepared ten achiral phase-transfer catalysts and showed that compound 33 with a quaternary ammonium centre, a urea group as a hydrogen bond donor and a 3,5-bis-trifluoromethylphenyl substituent was the most active catalyst for cyclic carbonate synthesis at 1 bar of carbon dioxide and 80 o C for 24 h. 82 Many terminal epoxides were converted into cyclic carbonates in 65-91% yields. When enantiomerically pure epoxides were used, cyclic carbonates were obtained with 67-99% enantiomeric excess.…”
Section: Pyridinium Saltsmentioning
confidence: 99%
“…More recently, Endo et al demonstrated that guanidinium iodide catalysts 32 were catalysts for the synthesis of cyclic carbonates under mild reaction conditions (1 bar carbon dioxide, 25 o C, 24 h, 5 mol% catalyst). 81 In 2019, Wang et al prepared ten achiral phase-transfer catalysts and showed that compound 33 with a quaternary ammonium centre, a urea group as a hydrogen bond donor and a 3,5-bis-trifluoromethylphenyl substituent was the most active catalyst for cyclic carbonate synthesis at 1 bar of carbon dioxide and 80 o C for 24 h. 82 Many terminal epoxides were converted into cyclic carbonates in 65-91% yields. When enantiomerically pure epoxides were used, cyclic carbonates were obtained with 67-99% enantiomeric excess.…”
Section: Pyridinium Saltsmentioning
confidence: 99%
“…[ 45,46 ] One of the most important ways to synthesize cyclic carbonate is cycloaddition of CO 2 and epoxide, in which these raw materials are low in price and high in atomic utilization, in accordance with the concept of green chemistry. [ 47‐50 ] The CO 2 cycloaddition reaction is generally considered to be activated by acid sites or acid‐base synergistic sites. [ 51,52 ] Here we classify these catalytic reactions according to the types of MOF acidic sites.…”
Section: Conversion Of Co2 To Fine Chemicalsmentioning
confidence: 99%
“…independently reported the use of related-bifunctional tetraalkylammonium halide catalysts bearing a thiourea or urea moiety for the synthesis of cyclic carbonate 1a under atmospheric CO 2 pressure. 13,14 Scheme 10. Other bifunctional quaternary onium salt catalysts…”
Section: Scheme 7 Initial Trial Of Bifunctional Quaternary Onium Salts By Wernermentioning
confidence: 99%